2014
DOI: 10.5194/nhess-14-901-2014
|View full text |Cite
|
Sign up to set email alerts
|

Ex post damage assessment: an Italian experience

Abstract: In recent years, awareness of a need for more effective disaster data collection, storage, and sharing of analyses has developed in many parts of the world. In line with this advance, Italian local authorities have expressed the need for enhanced methods and procedures for post-event damage assessment in order to obtain data that can serve numerous purposes: to create a reliable and consistent database on the basis of which damage models can be defined or validated; and to supply a comprehensive scenario of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 23 publications
0
77
0
5
Order By: Relevance
“…The type of recorded information is based on existing literature on flood damage surveys (e.g. Thieken et al, 2005;Schwarz and Maiwald, 2007;Merz et al, 2010;Molinari et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The type of recorded information is based on existing literature on flood damage surveys (e.g. Thieken et al, 2005;Schwarz and Maiwald, 2007;Merz et al, 2010;Molinari et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…On that occasion the regional CP asked Politecnico di Milano to develop a report (under construction) describing the event and its consequences at the regional level. Researchers activity focused on two aspects: (i) the development of an ex-post scenario to help CP to figure out event impacts [14], to identify priorities for recovery and reconstruction and to verify effectiveness of emergency plans; (ii) the development of an ex-ante scenario to be compared with the first to verify whether or not existing risk assessment and mitigation strategies are suitable to deal with flood risk in Umbria. Indeed, results from this experience are the starting point of Poli-RISPOSTA, allowing both to recognise needs and requirements in terms of data analysis and elaboration for the scenario development and to analyse the features of (available or required) data on which such activity should be performed (see section 3.2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the issues addressed by Daniell et al (2013) regarding the death toll of the 2010 Haiti earthquake are found to be related to accuracy problems. Similarly, the concerns in (Molinari et al 2014) regarding the usability of available flood damage data in Italy for loss assessment purposes are also found to be related to accuracy issues. Furthermore, even though the development of remote sensing technologies for disaster damage collection is growing fast, their reliability and accuracy is still an important factor to consider (e.g., see Joyce et al 2009;Liou et al 2012;Zhang et al 2013;Wang et al 2015;Foulser-Piggott et al 2016).…”
Section: Expressing the Uncertainty Of Disaster Loss Datamentioning
confidence: 99%